Silica Mineralization by a Peptide Template Having a High Charge Relay Effect. Issue 4 (1st April 2014) - Murai, Kazuki; Higuchi, Masahiro; Kuno, Tatsuya; Kato, Katsuya
Abstract The influence of the charge relay effects of peptide organic templates on silica mineralization has been investigated. β‐Sheet‐type peptide showed higher catalytic activity towards the condensation of trimethylsilanol than random‐coil peptides. The higher activity of the β‐sheet peptide was attributed to an effective charge relay effect between the His and Glu residues of the β‐sheet assembly. Furthermore, the silica mineralized on the VHVEVS peptide template formed a flat surface, which was affected by the peptide morphology. This result implied that the growth of the silica occurred at the surface of the peptide template in a manner very similar to that of the enzyme reaction. Thus, by using a specific structural design strategy, this process could be used for the preparation of specific silica particles.